INTEGRATION OF ABRASION DISASTER MITIGATION AND ECOTOURISM IN COASTAL COMMUNITY EMPOWERMENT (CASE STUDY AT KERTOMULYO BEACH GUYANGAN PATI) - Arsita Mutiara Nadila; Nur Eka Tsamrotun Ni’mah; Dany Miftah M. Nur (International Journal of Multidisciplinary Reseach, 2025)
Kertomulyo Beach in Pati Regency, Central Java, faces major challenges due to abrasion that threatens the coastal ecosystem and the livelihoods of local communities. This study aims to examine the role of mangrove ecosystems in abrasion mitigation and the potential for developing mangrove-based ecotourism. This study uses a descriptive qualitative method with a focus on community empowerment through enabling, empowering, and protecting. The results of the study indicate that the existence of mangrove forests is not only effective in reducing the impact of abrasion, but also has the potential to become an ecotourism attraction that improves the economic welfare of coastal communities. In conclusion, the integration of abrasion mitigation and mangrove-based ecotourism is an important sustainable strategy to be implemented at Kertomulyo Beach.